Facilitating conditions as predictor for the use of library technology by academic librarians in the Federal Capital Territory, Abuja (Lead City International Journal of Library, Information & Communication Sciences, 2024)
The use of technology has become non-negotiable for academic libraries aiming toprovide cutting edge services to their clientele. However, evidence shows that the use of technology by library personnel may depend on various factors. This study therefore investigates the influence of facilitating conditions as a predictor for the use of library technology by academic librarians in Federal Capital Territory, Abuja Nigeria. The study adopted a descriptive research survey design. The population of the study consists of all library personnel (Librarians and Library Officers) in universities in the Federal Capital Territory, Abuja. Total enumeration was used due to the size of the population. A structured questionnaire adapted from existing studies was used for data collection. The study found a moderate level of technology usage among academic librarians in the Federal Capital Territory, Nigeria (Mean = 2.96), and perceived facilitating condition (Mean = 3.14). The test of hypothesis revealed that facilitating condition (R2 = 0.265, p<0.05)have significant influence on the use of technology among the respondents. The study concluded that there are still some underlying factors that must be addressed before academic libraries in the FCT can reach the level of technology use that will enable them provide world class library services. It was therefore recommended that Universities in the FCT has work hand in hand with the management of their academic libraries to invest in relevant technologies needed in the provision of modern information service delivery